Preparation method and application of heavy metal ion electrochemical sensor

ZnCo/N-PC material prepared by hydrothermal-high temperature cracking is combined with activated carbon to construct a ZnCo/N-PC@NACS/GCE electrochemical sensor, which solves the problems of complex preparation and low sensitivity in the prior art, and achieves rapid and sensitive detection of Pb2+ and Cd2+, which is suitable for water samples and grain samples.

CN120559043APending Publication Date: 2025-08-29HENAN INST OF SCI & TECH
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202510742358.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-08-29

Smart Images

  • Figure CN120559043A_ABST
    Figure CN120559043A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a heavy metal ion electrochemical sensor, and the method comprises the following steps: firstly synthesizing a zinc-cobalt-nitrogen co-doped material by a hydrothermal method, then preparing ZnCo / N-PC from the material by a high-temperature carbonization method, and then compounding the ZnCo / N-PC and NACS by a physical mixing method to obtain the heavy metal ion electrochemical sensor. And modifying an electrochemical sensor electrode by a dispensing method to obtain the ZnCo / N-PC coated NACS / GCE ion electrochemical sensor. The electrochemical sensor constructed by the invention can realize rapid, sensitive, selective and synchronous determination of Pb < 2 + > and Cd < 2 + >, and can be successfully used for effective determination of Pb < 2 + > and Cd < 2 + > in actual samples such as water samples and grains.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heavy metal ion electrochemical sensors, and in particular relates to a preparation method and application of a heavy metal ion electrochemical sensor. Background Art

[0002] Currently, common methods for detecting heavy metal ions include atomic fluorescence spectrometry, inductively coupled plasma-mass spectrometry, inductively coupled plasma-atomic emission spectrometry, high-performance liquid chromatography, and enzyme analysis. However, these methods are often costly, complex, or lack sensitivity. In contrast, electrochemical sensors offer advantages such as fast response, ease of operation, low cost, portability, and suitability for on-site monitoring and rapid in-situ analysis.

[0003] A commonly used method for electrochemical detection of heavy metal ions is anodic stripping voltammetry, which involves two key processes: enrichment and stripping. During the enrichment phase, a negative potential is applied to the working electrode, driving the target ions to deposit on its surface. During the stripping phase, the electrode potential is swept in the positive direction, causing the deposited metal ions to be reoxidized and stripped from the electrode surface. Therefore, in electrochemical sensors, electrode modification materials play a key role in the enrichment and detection of heavy metal ions. Among the known technologies, patent document CN202211432410.4 discloses a MOFs@nanofiber carbon aerogel, its preparation method, and its application in an electrochemical heavy metal ion detection sensor. Specifically, it discloses adding MOFs to an electrospinning precursor solution, preparing uniform MOF-inlaid nanofibers through electrospinning technology, and further pre-oxidizing and carbonizing to obtain MOFs@nanofiber carbon aerogel with a large specific surface area, low density, high porosity, and a 3D network structure. This is then used as an electrode modification material to prepare a sensor for detecting heavy metal ions. Patent document CN202311013874.6 discloses a bismuth-doped high-performance electrocatalytic composite material, a preparation method and an application thereof, and specifically discloses that the Bi / Bi2WO6 composite material is applied to the surface modification of the working electrode after forming a film to achieve the Cd 2+ , Pb 2+ Synchronous detection of the sensor for Cd 2+ The linear range of detection is 0.3~30μM, for Pb 2+The linear range of detection is 0.4 to 30 μM. Although the above-mentioned prior art can simultaneously detect the content of lead and cadmium in the sample, there are still problems such as the preparation method of the electrochemical sensor electrode material is relatively complicated, the linear range of the method is narrow, and the sensitivity is not high. The patent document CN201911204276.0 discloses an electrochemical method for detecting trace lead ions by using a working electrode modified with cobalt-nitrogen doped carbon material. It mainly integrates the advantages of bimetallic zeolite imidazole compounds and oxidatively modified carbon tubes. Cobalt-nitrogen doped carbon materials are prepared through chemical reactions and tubular furnace sintering. The evaporation of zinc metal in the material produces more pores, exposing more active sites in the material. The presence of carbon tubes effectively improves the conductivity and specific surface area of ​​the material. The material is modified into a glassy carbon electrode, and trace lead ions in water can be efficiently detected by differential pulse anodic stripping voltammetry. Under optimal conditions, the detection limit reaches 0.4 μg L -1 , linear range 0.2-70 μg L -1 Although this method has high sensitivity to lead ions, it only detects one type of heavy metal, lead ions. Furthermore, the preparation process involves steps such as nitric acid oxidation, solvent thermal reaction, and high-temperature cracking. The operation is relatively complex and uses concentrated acid and methanol, making it less environmentally friendly. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the present invention provides a preparation method and application of heavy metal ion electrochemical sensor. In this method, zinc and cobalt are used as metal sources and water is used as solvent. A three-dimensional layered bird's nest-shaped ZnCo / N-PC is prepared by hydrothermal-pyrolysis method. The ZnCo / N-PC is then composited with activated carbon (NACS) and then modified on glassy carbon electrode (GCE) to obtain ZnCo / N-PC@NACS / GCE electrochemical sensor. The electrochemical sensor has good performance in the presence of Pb 2+ 、Cd 2+ The preparation method firstly synthesizes the zinc-cobalt-nitrogen co-doped material by hydrothermal method, then prepares ZnCo / N-PC by high temperature carbonization method, then composites ZnCo / N-PC with NACS by physical mixing method, and then modifies the electrochemical sensor electrode by drop coating method. The electrochemical sensor constructed by the present invention can realize the detection of Pb 2+ 、Cd 2 + It is a rapid, sensitive, selective and synchronous determination method and can be successfully used for the determination of Pb in water samples, grains and other actual samples. 2+ 、Cd 2+ effective determination.

[0005] The present invention adopts the following technical solution to solve the above technical problems: a method for preparing a heavy metal ion electrochemical sensor, the specific preparation steps of which are:

[0006] Step S1: Pretreatment of glassy carbon electrode

[0007] The glassy carbon electrode is polished with aluminum oxide polishing powder, and then rinsed with ultrapure water until no aluminum oxide polishing powder remains on the surface of the glassy carbon electrode. The glassy carbon electrode is then baked with an infrared lamp until it is dry to obtain a pretreated glassy carbon electrode.

[0008] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0009] A mixed metal salt of (CH3COO)2Zn·2H2O and Co(NO3)2·6H2O and 2-methylimidazole are dissolved in deionized water to obtain a mixed metal salt solution and a 2-methylimidazole solution, respectively. The mixed metal salt solution and the 2-methylimidazole solution are then mixed and stirred at room temperature to mix uniformly. The reaction solution is centrifuged at 8000-10000 rpm for 5-10 minutes to obtain a purple precipitate. The purple precipitate is washed three times with deionized water and ethanol, and dried in a vacuum drying oven overnight to obtain a zinc-cobalt-nitrogen co-doped material.

[0010] Step S3: Preparation of ZnCo / N-PC

[0011] The zinc-cobalt-nitrogen co-doped material obtained in step S2 is placed in a tube furnace, heated to 600-900° C. in a N2 environment, and carbonized at this temperature for 1-5 hours to obtain ZnCo / N-PC;

[0012] Step S4: Preparation of ZnCo / N-PC@NACS

[0013] The ZnCo / N-PC obtained in step S3 is mixed with NACS to obtain a ZnCo / N-PC@NACS composite material; Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0014] The ZnCo / N-PC@NACS composite material obtained in step S4 was dispersed in a solvent and ultrasonically treated for 5 to 15 minutes to obtain a black suspension, i.e., the modification solution. The modification solution was then pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The ZnCo / N-PC@NACS / GCE ion electrochemical sensor was then baked with an infrared lamp until a thin film was formed on the electrode surface.

[0015] It is further defined that the molar ratio of zinc to cobalt in the mixed metal salt in step S2 is 1 to 10:1.

[0016] It is further defined that the molar ratio of the mixed metal salt to 2-methylimidazole in step S2 is 1:4-8, and the total molar concentration of the mixed metal salt in the mixed metal salt solution is 0.05-0.1 mol / L.

[0017] It is further defined that in step S2, the stirring speed is 700-900 rpm, and the stirring time is 6-48 hours.

[0018] It is further defined that the mass ratio of ZnCo / N-PC to NACS in step S4 is 1:0.1-5.

[0019] It is further defined that the solvent in step S4 is water, DMF, ethanol or chitosan acetate solution.

[0020] It is further defined that the concentration of the modification solution in step S5 is 0.5 to 2.5 mg / mL, and the amount of the modification solution applied to the surface of the pretreated glassy carbon electrode is 1 to 10 μL.

[0021] Application of ZnCo / N-PC@NACS electrochemical sensor prepared based on the above method in heavy metal ion electrochemical sensor.

[0022] The ZnCo / N-PC@NACS electrochemical sensor prepared based on the above method was used for the simultaneous and selective detection of heavy metal ions Pb 2+ and Cd 2+ .

[0023] The ZnCo / N-PC@NACS electrochemical sensor prepared based on the above method was used to simultaneously and selectively detect heavy metal ions Pb in water samples or grains. 2+ and Cd 2+ .

[0024] Compared with the prior art, the present invention has the following technical advantages and beneficial effects:

[0025] 1. The present invention prepares ZnCo / N-PC using zinc and cobalt as metal sources and water as solvent to synthesize a zinc-cobalt-nitrogen co-doped material. Subsequently, the material is carbonized at 600-900°C to obtain a three-dimensional layered, bird's-nest-shaped ZnCo / N-PC. Since zinc has a boiling point of 907°C, this invention cleverly utilizes the volatilization effect of metallic zinc to implement a "dynamic pore-forming" strategy. The small amount of Zn and Co remaining after volatilization can form highly dispersed metal sites, enhancing activity and ensuring coordinated regulation of pores and active sites. This significantly improves heavy metal ion enrichment and electrocatalytic performance, ultimately increasing detection sensitivity.

[0026] 2. The ZnCo / N-PC prepared by the present invention contains zinc, cobalt and nitrogen. The Lewis acidity of Zn enhances the electrochemical sensor's sensitivity to the target ion Pb. 2+ 、Cd 2+ The high content of pyridinic nitrogen and graphitic nitrogen regulates the electron distribution of the carbon matrix, optimizes the d-band center of the metal site, and enhances the adsorption of Pb 2+ 、Cd 2+In addition, the three-dimensional layered bird's nest structure also plays a certain nano-confinement effect on heavy metal ions. Therefore, it can significantly improve the coordination capacity of heavy metal ions Pb 2+ 、Cd 2+ The capture ability of the electrochemical sensor is improved, thereby improving the selectivity of the electrochemical sensor.

[0027] 3. The NACS used in the present invention has an ultra-high specific surface area and abundant micropores, allowing it to load a large amount of target ions. Furthermore, it is highly conductive, facilitating the rapid enrichment of heavy metal ions and promoting rapid charge transfer, which facilitates the redox reaction of heavy metal ions.

[0028] 4. Compared with the electrodes prepared from ZnCo / N-PC and NACS single materials, the ZnCo / N-PC@NACS / GCE prepared in this invention has a better effect on the target material Pb 2+ 、Cd 2+ It has higher detection sensitivity. Among them, ZnCo / N-PC has a mesoporous structure and NACS has a microporous structure: ZnCo / N-PC@NACS constructs a "high-speed channel + high sample loading" model. The mesopores act as "ion highways" to accelerate mass transfer, and the micropores act as "adsorption warehouses" to enrich target ions. The two work together to achieve rapid response and high sensitivity. In addition, the ZnCo / N-PC pyrolytic carbon skeleton provides mechanical support to prevent the electrode material from collapsing during recycling. NACS fills the ZnCo / N-PC mesoporous gaps, reduces material agglomeration, and maintains pore connectivity. The structural rigidity of ZnCo / N-PC and the flexible filling effect of NACS make the ZnCo / N-PC@NACS composite electrode more mechanically stable.

[0029] 5. The present invention improves the material synthesis route and optimizes the experimental parameters, and finally achieves Pb under the optimal conditions of static time, enrichment potential, enrichment time, drop coating amount, etc. 2+ 、Cd 2+ Simultaneous detection was achieved with a wide linear range (0.1-80 μM) and a low detection limit (0.072 μM, 0.039 μM).

[0030] 6. The present invention can not only realize the detection of Pb in simple water sample environment (tap water, lake water) 2+ 、Cd 2+ It can also detect Pb in cereals (millet, rice) with complex ingredients and severe matrix interference. 2+ 、Cd 2+ The electrochemical sensor can be used for quantitative detection. For different samples, it demonstrates satisfactory recovery, precision, selectivity, and stability. This provides strong technical support for rapid water quality assessment and ecological monitoring.

[0031] 7. Compared with the patent document CN2019112042760, the present invention uses water as solvent and adopts hydrothermal-pyrolysis method to prepare three-dimensional layered bird's nest type ZnCo / N-PC, while retaining zinc, cobalt and nitrogen elements. The small amount of Zn and Co remaining after volatilization may form highly dispersed metal sites, enhance activity, ensure pore-active site coordinated regulation, and significantly improve the resistance to heavy metal ions Pb 2+ 、Cd 2+ The Lewis acidity of Zn enhances the sensitivity of electrochemical sensors to the target ion Pb. 2+ 、Cd 2+ The high content of pyridinic nitrogen and graphitic nitrogen regulates the electron distribution of the carbon matrix, optimizes the d-band center of the metal site, and enhances the adsorption of Pb 2+ 、Cd 2+ Therefore, the capture ability of heavy metal ions can be significantly improved, that is, the selectivity of the sensor can be improved. In addition, the preparation process is simple, green and environmentally friendly, and can achieve Pb 2+ 、Cd 2+ Simultaneous determination of two heavy metal ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 are SEM images of different samples, where (a) is the SEM image of ZnCo / N-PC, (b) is the SEM image of NACS, and (c) is the SEM image of ZnCo / N-PC@NACS.

[0033] Figure 2 The electrochemical sensors prepared in Examples 1 to 4 and Comparative Examples 1 to 3 react with heavy metal ions Pb 2+ 、Cd 2+ Comparison chart of SWV tested.

[0034] Figure 3 (a) is the ZnCo / N-PC@NACS / GCE to 0.1~80μM Pb 2+ 、Cd 2+ Quantitative detection chart of Figure 3 Middle (b) is a linear relationship diagram between concentration and peak current value established by quantitative detection.

[0035] Figure 4 ZnCo / N-PC@NACS / GCE in the presence of 10 μM Pb 2+ 、Cd 2+ SWV detection diagram of other interfering ions added to the acetic acid / sodium acetate buffer solution.

[0036] Figure 5(a), (c), (e), and (g) are the results of the standard addition method using ZnCo / N-PC@NACS / GCE to analyze the Pb content in four real samples: tap water, lake water, millet, and rice. 2+ 、Cd 2+ SWV diagram for detection, Figure 5 (b), (d), (f), and (h) are the linear relationship diagrams between the actual sample concentration and the peak current value. DETAILED DESCRIPTION

[0037] The present invention prepares ZnCo / N-PC by hydrothermal-pyrolysis method, and modifies glassy carbon electrode after compounding it with NACS to prepare electrochemical sensor, which effectively improves the poor conductivity of bare glassy carbon electrode and improves the detection performance of electrochemical sensor for Pb 2+ 、Cd 2+ sensitivity.

[0038] The present invention specifically prepares an electrochemical sensor by the following method, comprising the following steps:

[0039] Step S1: Pretreatment of glassy carbon electrode

[0040] With the help of alumina polishing powder, the glassy carbon electrode was placed on the suede and polished in the shape of an "8" for about 5 minutes. It was then rinsed with ultrapure water until there was no residual alumina polishing powder on the surface of the glassy carbon electrode. It was then baked with an infrared lamp until the glassy carbon electrode was dry to obtain a pretreated glassy carbon electrode.

[0041] Step S2: Preparation of zinc-cobalt-nitrogen doped materials

[0042] A mixed metal salt of (CH3COO)2Zn·2H2O and Co(NO3)2·6H2O (the molar ratio of the mixed metal salt can be 1-10:1) and 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole can be 1:4-8) are dissolved in two portions of deionized water, respectively, to a molar concentration of 0.05-0.1 mol / L. The two solutions are mixed and stirred thoroughly at room temperature (the stirring speed can be 700-900 rpm and the stirring time can be 6-48 hours). The reaction solution is then centrifuged thoroughly (the centrifugal speed can be 8000-10000 rpm and the centrifugal time can be 5-10 minutes) to obtain a purple precipitate. The purple precipitate is washed three times with deionized water and ethanol, and dried in a vacuum drying oven overnight to obtain a zinc-cobalt-nitrogen co-doped material.

[0043] Step S3: Preparation of ZnCo / N-PC

[0044] The zinc-cobalt-nitrogen co-doped material obtained in step S2 is placed in a tube furnace, slowly heated to a certain temperature (the carbonization temperature can be selected to be 600-900°C) in an N2 environment, and maintained at the high temperature for a period of time (the carbonization time can be selected to be 1-5 hours) to obtain ZnCo / N-PC.

[0045] Step S4: Preparation of ZnCo / N-PC@NACS

[0046] The ZnCo / N-PC obtained in step S3 is uniformly mixed with NACS in a certain mass ratio (the mixing mass ratio can be selected to be 1:0.1 to 5) to obtain ZnCo / N-PC@NACS.

[0047] Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0048] The ZnCo / N-PC@NACS obtained in step S4 is dissolved in DMF and fully ultrasonically oscillated (the ultrasonic oscillation time can be optionally 5 to 15 minutes) to obtain a black suspension, i.e., the modification solution. The modification solution (the concentration of the modification solution can be optionally 0.5 to 2.5 mg / mL) is pipetted (the amount of the pipetted solution can be optionally 1 to 10 μL) and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. Subsequently, the ZnCo / N-PC@NACS / GCE electrochemical sensor is obtained by baking with an infrared lamp until a thin film is formed on the electrode surface.

[0049] The electrochemical sensor prepared by the above method can be further applied to heavy metal Pb 2+ 、Cd 2+ Simultaneous detection.

[0050] In order to better illustrate the above technical solution, the above solution is described in detail below in conjunction with specific embodiments. However, this should not be understood as limiting the scope of the above subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.

[0051] Example 1

[0052] Step S1: Pretreatment of glassy carbon electrode

[0053] With the help of alumina polishing powder, the glassy carbon electrode was placed on the suede and polished in the shape of an "8" for about 5 minutes. It was then rinsed with ultrapure water until there was no residual alumina polishing powder on the surface of the glassy carbon electrode. It was then baked with an infrared lamp until the glassy carbon electrode was dry to obtain a pretreated glassy carbon electrode.

[0054] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0055] Dissolve 1.5238g of a mixed metal salt of (CH3COO)2Zn·2H2O and 0.2183g of Co(NO3)2·6H2O and 2.05g of 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole was 1:4.17) in two 75mL portions of deionized water. The two solutions were mixed and stirred at 800 rpm for 36 hours at room temperature. The reaction solution was then centrifuged at 8000 rpm for 5 minutes to obtain a purple precipitate. The purple precipitate was washed three times with deionized water and ethanol and dried in a vacuum oven overnight to obtain the zinc-cobalt-nitrogen co-doped material.

[0056] Step S3: ZnCo / N-PC preparation

[0057] The zinc-cobalt-nitrogen co-doped material obtained in step S2 was placed in a tube furnace, slowly heated to 900° C. in an N 2 environment, and maintained at this temperature for carbonization for 3 h to obtain ZnCo / N-PC.

[0058] Step S4: Preparation of ZnCo / N-PC@NACS

[0059] The ZnCo / N-PC obtained in step S3 was mixed with NACS in a mass ratio of 1:1 to obtain ZnCo / N-PC@NACS.

[0060] Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0061] 2 mg of the ZnCo / N-PC@NACS obtained in step S4 was weighed and dissolved in 1 mL of DMF and ultrasonically shaken for 10 min to obtain a black suspension, namely the modification solution. 7 μL of the modification solution was pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The electrode was then baked with an infrared lamp until a thin film was formed on the surface of the electrode to obtain the ZnCo / N-PC@NACS / GCE electrochemical sensor.

[0062] Example 2

[0063] Step S1: Pretreatment of the glassy carbon electrode, same as in Example 1.

[0064] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0065] A mixed metal salt of 1.524 g (CH₃COO)₂Zn·2H₂O and 0.2183 g Co(NO₃)₂·6H₂O and 2.05 g 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole was 1:4.17) were dissolved in two 75 mL portions of deionized water. The two solutions were mixed and stirred at 700 rpm for 36 hours at room temperature. The reaction solution was then centrifuged at 8000 rpm for 5 minutes to obtain a purple precipitate. The purple precipitate was washed three times with deionized water and ethanol and dried in a vacuum oven overnight to obtain the zinc-cobalt-nitrogen co-doped material.

[0066] Step S3: Preparation of ZnCo / N-PC

[0067] The zinc-cobalt-nitrogen co-doped material obtained in step S2 was placed in a tube furnace, slowly heated to 900° C. in an N 2 environment, and maintained at this temperature for carbonization for 3 h to obtain ZnCo / N-PC.

[0068] Step S4: Preparation of ZnCo / N-PC@NACS

[0069] The ZnCo / N-PC obtained in step S3 was mixed with NACS in a mass ratio of 3:1 to obtain ZnCo / N-PC@NACS.

[0070] Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0071] 2 mg of ZnCo / N-PC@NACS obtained in step S4 was weighed and dispersed in 1 mL of DMF and ultrasonically vibrated for 10 min to obtain a black suspension, i.e., the modification solution. 5 μL of the modification solution was pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The solution was then baked with an infrared lamp until a thin film was formed on the surface of the glassy carbon electrode to obtain the ZnCo / N-PC@NACS / GCE electrochemical sensor.

[0072] Example 3

[0073] Step S1: pre-treating the surface of the glassy carbon electrode, as in Example 1.

[0074] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0075] A mixed metal salt of 1.524 g (CH3COO)2Zn·2H2O and 0.2183 g Co(NO3)2·6H2O and 2.05 g 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole was 1:4.17) was dissolved in two 75 mL portions of deionized water. The two solutions were mixed and stirred at 900 rpm for 36 hours at room temperature. The reaction solution was then centrifuged at 8000 rpm for 5 minutes to obtain a purple precipitate. The purple precipitate was washed three times with deionized water and ethanol, respectively, and dried in a vacuum oven overnight to obtain the zinc-cobalt-nitrogen co-doped material.

[0076] Step S3: Preparation of ZnCo / N-PC

[0077] The zinc-cobalt-nitrogen co-doped material obtained in step S2 was placed in a tube furnace, slowly heated to 900° C. in an N 2 environment, and maintained at this temperature for carbonization for 3 h to obtain ZnCo / N-PC.

[0078] Step S4: Preparation of ZnCo / N-PC@NACS

[0079] The ZnCo / N-PC obtained in step S3 was mixed with NACS in a mass ratio of 1:3 to obtain ZnCo / N-PC@NACS.

[0080] Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0081] 2 mg of the ZnCo / N-PC@NACS obtained in step S4 was weighed and dissolved in 1 mL of DMF and ultrasonically shaken for 10 min to obtain a black suspension, namely the modification solution. 5 μL of the modification solution was pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The electrode was then baked with an infrared lamp until a thin film was formed on the surface to obtain the ZnCo / N-PC@NACS / GCE electrochemical sensor.

[0082] Example 4

[0083] Step S1: pre-treating the surface of the glassy carbon electrode, as in Example 1.

[0084] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0085] Dissolve 1.0975g of a mixed metal salt of (CH3COO)2Zn·2H2O and 0.2910g of Co(NO3)2·6H2O, and 2.05g of 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole was 1:4.17) in two 75mL portions of deionized water. The two solutions were mixed and stirred at 800 rpm for 36 hours at room temperature. The reaction solution was then centrifuged at 8000 rpm for 5 minutes to obtain a purple precipitate. The purple precipitate was washed three times with deionized water and ethanol, respectively, and dried in a vacuum oven overnight to obtain a zinc-cobalt-nitrogen co-doped material.

[0086] Step S3: Preparation of ZnCo / N-PC

[0087] The zinc-cobalt-nitrogen co-doped material obtained in step S2 was placed in a tube furnace, slowly heated to 900° C. in an N 2 environment, and maintained at this temperature for carbonization for 3 h to obtain ZnCo / N-PC.

[0088] Step S4: Preparation of ZnCo / N-PC@NACS

[0089] The ZnCo / N-PC obtained in step S3 was mixed with NACS in a mass ratio of 1:1 to obtain ZnCo / N-PC@NACS.

[0090] Step S5: Preparation of ZnCo / N-PC@NACS / GCE

[0091] 2 mg of the ZnCo / N-PC@NACS obtained in step S4 was weighed and dissolved in 1 mL of DMF and ultrasonically shaken for 10 min to obtain a black suspension, i.e., the modification solution. 5 μL of the modification solution was pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The electrode was then baked with an infrared lamp until a thin film was formed on the surface of the electrode to obtain the ZnCo / N-PC@NACS / GCE electrochemical sensor.

[0092] Comparative Example 1 (ZnCo / N-PC not added to the electrode modification material)

[0093] Step S1: pre-treating the surface of the glassy carbon electrode, as in Example 1.

[0094] Step S2: Preparation of novel activated carbon electrodes for supercapacitors

[0095] NACS was thoroughly ground into powder using a mortar, 2 mg was weighed and placed in a centrifuge tube, added to 1 mL of DMF, and ultrasonically shaken for 10 min to obtain a black suspension, i.e., the modification solution. 5 μL of the modification solution was pipetted with a pipette and evenly applied to the surface of the pretreated glassy carbon electrode obtained in step S1. It was then baked with an infrared lamp until a thin film was formed on the electrode surface to obtain a new activated carbon electrode for supercapacitors.

[0096] Comparative Example 2 (NACS not added to the electrode modification material)

[0097] Step S1: pre-treating the surface of the glassy carbon electrode, as in Example 1.

[0098] Step S2: Preparation of zinc-cobalt-nitrogen co-doped material

[0099] A mixed metal salt of 1.524 g (CH3COO)2Zn·2H2O and 0.2183 g Co(NO3)2·6H2O and 2.05 g 2-methylimidazole (the molar ratio of the mixed metal salt to 2-methylimidazole was 1:4.17) was dissolved in two 75 mL portions of deionized water. The two solutions were mixed and stirred at 800 rpm for 36 hours at room temperature. The reaction solution was then centrifuged at 8000 rpm for 5 minutes to obtain a purple precipitate. The purple precipitate was washed three times with deionized water and ethanol, respectively, and dried in a vacuum oven overnight to obtain the zinc-cobalt-nitrogen co-doped material.

[0100] Step S3: Preparation of ZnCo / N-PC

[0101] The zinc-cobalt-nitrogen co-doped material obtained in step S2 was placed in a tube furnace, slowly heated to 900° C. in an N 2 environment, and maintained at this temperature for carbonization for 3 h to obtain ZnCo / N-PC.

[0102] Step S4: Preparation of ZnCo / N-PC / GCE

[0103] 2 mg of the zinc-cobalt ZnCo / N-PC obtained in step S3 was weighed and dispersed in 1 mL of DMF and ultrasonically shaken for 10 min to obtain a black suspension, i.e., the modification solution. 5 μL of the modification solution was pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The electrode was then baked with an infrared lamp until a thin film was formed on the surface to obtain the ZnCo / N-PC / GCE electrochemical sensor.

[0104] Comparative Example 3 (ZnCo / N-PC@NACS was not added to the electrode modification material, i.e., a bare glassy carbon electrode)

[0105] Step S1: pre-treating the surface of the glassy carbon electrode, as in Example 1.

[0106] Product performance test:

[0107] In the presence of 10 μM Pb 2+ 、Cd 2+ Acetic acid / sodium acetate buffer solution was used to detect Pb 2+ 、Cd 2+ Quantitative detection of .

[0108] from Figure 1The SEM results of (a) show that the ZnCo / N-PC synthesized according to step S2 in Example 1 presents a three-dimensional layered bird's nest shape with uniform particle size. Figure 1 From the SEM results in (b), it can be seen that NACS presents an irregular granular structure. Figure 1 From the SEM results in (c), it can be seen that the ZnCo / N-PC@NACS prepared according to Example 1 contains both three-dimensional layered bird's nest-shaped ZnCo / N-PC and irregular granular structured NACS.

[0109] from Figure 2 The results of electrochemical determination of heavy metals show that the ZnCo / N-PC / GCE prepared in Example 1 of the present invention has a strong electrochemical effect on Pb 2+ 、Cd 2+ The peak current value of the response I p Largest, most sensitive.

[0110] from Figure 3 It can be seen that with the increase of Pb 2+ 、Cd 2+ As the concentration increases, the oxidation peak current value increases regularly, showing a good linear relationship, a wide linear range, and a low detection limit.

[0111] from Figure 4 According to the results of electrochemical detection of heavy metals, the same concentration of Fe 2+ 、Fe 3+ , K + 、Na + 、Zn 2+ The sensor detects Pb 2+ 、Cd 2+ The effect of α on the surface of the electrochemical sensor is small, indicating that the electrochemical sensor has high selectivity.

[0112] from Figure 5 As shown in Table 1, the prepared electrochemical sensor can be successfully used to detect Pb in actual samples such as tap water, lake water, millet, and rice using the standard addition method. 2+ 、Cd 2+ Good spiked recoveries were obtained for the four actual samples.

[0113] Table 1 Quantitative detection of four actual samples by standard addition method

[0114]

[0115] Based on the above test results, it can be seen that the present invention can achieve the control of the microscopic properties of ZnCo / N-PC and the rapid and efficient identification and detection of heavy metal Pb in ZnCo / N-PC@NACS composite materials by adjusting the ratio of metal salts, adjusting the composite ratio of ZnCo / N-PC and NACS, optimizing the drop coating amount and other key factors. 2+ 、Cd 2+ The electrochemical sensor constructed in Example 1 of the present invention can be applied to the detection of trace heavy metal ions in actual water samples and grains. However, the electrodes prepared using a single material (Comparative Examples 1 to 3) are sensitive to heavy metal ions Pb. 2+ 、Cd 2+ The sensitivity is low, and when certain parameters are not optimized during the preparation process (Examples 2 to 4), the optimal electrochemical detection effect cannot be achieved.

[0116] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a heavy metal ion electrochemical sensor, characterized in that The specific preparation steps are: Step S1: Pretreatment of glassy carbon electrode The glassy carbon electrode is polished with aluminum oxide polishing powder, and then rinsed with ultrapure water until no aluminum oxide polishing powder remains on the surface of the glassy carbon electrode. The glassy carbon electrode is then baked with an infrared lamp until it is dry to obtain a pretreated glassy carbon electrode. Step S2: Preparation of zinc-cobalt-nitrogen co-doped material A mixed metal salt of (CH3COO)2Zn·2H2O and Co(NO3)2·6H2O and 2-methylimidazole are dissolved in deionized water to obtain a mixed metal salt solution and a 2-methylimidazole solution, respectively. The mixed metal salt solution and the 2-methylimidazole solution are then mixed and stirred at room temperature to mix uniformly. The reaction solution is centrifuged at 8000-10000 rpm for 5-10 minutes to obtain a purple precipitate. The purple precipitate is washed three times with deionized water and ethanol, and dried in a vacuum drying oven overnight to obtain a zinc-cobalt-nitrogen co-doped material. Step S3: Preparation of ZnCo / N-PC The zinc-cobalt-nitrogen co-doped material obtained in step S2 is placed in a tube furnace, heated to 600-900° C. in a N 2 environment, and carbonized at this temperature for 1-5 hours to obtain ZnCo / N-PC; Step S4: Preparation of ZnCo / N-PC@NACS The ZnCo / N-PC obtained in step S3 is mixed with NACS to obtain a ZnCo / N-PC@NACS composite material; Step S5: Preparation of ZnCo / N-PC@NACS / GCE The ZnCo / N-PC@NACS composite material obtained in step S4 was dispersed in a solvent and ultrasonically treated for 5 to 15 minutes to obtain a black suspension, i.e., the modification solution. The modification solution was then pipetted with a pipette and evenly drop-coated on the surface of the pretreated glassy carbon electrode obtained in step S1. The ZnCo / N-PC@NACS / GCE ion electrochemical sensor was then baked with an infrared lamp until a thin film was formed on the electrode surface.

2. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: The molar ratio of zinc to cobalt in the mixed metal salt in step S2 is 1-10:

1.

3. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: The molar ratio of the mixed metal salt to 2-methylimidazole in step S2 is 1:4-8, and the total molar concentration of the mixed metal salt in the mixed metal salt solution is 0.05-0.1 mol / L.

4. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: In step S2, the stirring speed is 700-900 rpm, and the stirring time is 6-48 h.

5. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: The mass ratio of ZnCo / N-PC to NACS in step S4 is 1:0.1-5.

6. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: step The solvent in S4 is water, DMF, ethanol or chitosan acetate solution.

7. The method for preparing a heavy metal ion electrochemical sensor according to claim 1, wherein: The concentration of the modification solution in step S5 is 0.5-2.5 mg / mL, and the amount of the modification solution applied to the surface of the pretreated glassy carbon electrode is 1-10 μL.

8. Use of the ZnCo / N-PC@NACS electrochemical sensor prepared according to the method according to any one of claims 1 to 6 in a heavy metal ion electrochemical sensor.

9. ZnCo / N-PC@NACS electrochemical sensor prepared according to the method of any one of claims 1 to 6 for simultaneous selective detection of heavy metal ions Pb 2+ and Cd 2+ .

10. The ZnCo / N-PC@NACS electrochemical sensor prepared according to the method of any one of claims 1 to 6 is used for the simultaneous selective detection of heavy metal ions Pb in water samples or grains 2+ and Cd 2+ .